Recovering police legitimacy: a radical framework - McGregor, Rafe (Routledge, 2025)
"Legitimacy is lost when the police either fail to protect the public or rely on coercion rather than consent to achieve that protection. Recovering Police Legitimacy challenges conventional criminological, political, and public solutions to the problem by approaching it from the bottom up"--